EXAMINATION OF THE ADEQUACY OF RESOURCES PREPAREDNESS FOR IMPLEMENTATION OF INTEGRATION OF DIGITAL LEARNING IN PUBLIC PRIMARY SCHOOLS IN MERU COUNTY, KENYA - Kaaria Kiugu, Dr David; Kibaara , Dr Tarsilla; Wachira, Dr Rebecca (African Journal of Education and Practice, 2021)
Purpose: Digital learning integration (DLI) in schools has positive implications for the education systems. DLI programme was rolled out in Meru County alongside other 46 counties in Kenya in 2016 after several postponements. However, DLI programme adoption is attributed to preparation challenges. This study examined the adequacy of resources on implementation of DLI programme in public primary schools in Meru County. Methodology: The study was guided by Roger's diffusion of innovation theory and Boum's project management cycle. The study used descriptive survey design and adopted mixed method approach. The study targeted 710 public primary schools in 9 sub-counties. Data was provided by 710 head teachers, 7032 teachers, 2004 Parent Teachers Association (PTA) executive members, and 25,720 grade 3 DLI programme pioneer pupils. A 10% sample of schools was considered sufficient which was obtained using simple random sampling technique. As a result, 71 head teachers and 703 teachers were obtained. Purposive judgmental sampling technique was used to get 201 PTA members. Further, Sloven's formula was used to get a sample size of 396 pupils that formed Focus Group Discussion (FGD) each consisting of 8 learners, and 9 SCDEs were purposively sampled. Questionnaires were used to collect data from head teachers, teachers and PTA while interview schedules and FGDs were used to get data from SCDEs and from learners respectively. Observational schedule was also used to provide guide for focusing observation and recording data. The research tools were pre-tested for validity and reliability. The quantitative data was analyzed using IBM SPSS Statistics for Windows version 22. The data was analyzed, interpreted and reported using percentages, measures of central tendency. Univariate regression analysis was used to test hypothesis. Qualitative data was analyzed according to themes based on study objective and reported in narratives. Findings: Through computation of Pearson product moment correlation coefficients confirmed that there is significant positive correlation (r = 0.825) between variable adequacy of digital learning resources against DLI at 0.05 level of significance. Resources such as tablets, internet connectivity, computer laboratory and electricity were noted to be inadequate. Learners who were introduced to DLI appreciated and were always eager to learn using the available digital technology resources. In addition, there was no monitoring or evaluation of the digital programme after roll out by quality assurance and standards officers as per the policy guidelines. The study concluded that preparations for digital programme were inadequate. The findings will be useful to educationists, parents, teachers, and policy makers. Unique contribution to theory, practice and policy: The study recommended that MoE should go back to the drawing board and come up with proactive measures on provision of digital learning resources. Adequate resources such as tablets, desks, computer laboratories, network connectivity and electricity among others should be availed to all schools. Tablets available are too few to be distributed to pupils during this period of COVID-19 pandemic leading to resource wastage. MoE should own the innovation and facilitate its full adoption by coming up with apt monitoring and control systems. Political objectives should not be allowed to overshadow policy structures such as planning, management and administrative processes.